The Influence of Service Quality and Price Towards The Customer Loyalty in Jinjja Chicken Medan - Gracia (PT FORMOSA CENDEKIA GLOBAL, 2022)
The culinary business is now rising year after year. Customers are vital to a company's survival and growth. Good service and reasonable prices will also impact customers' opinions and urge them to return. Loyal customers will boost sales and growth. This study looked at two independent factors and one dependent variable. This study will examine Jinjja Chicken, a trendy Korean restaurant in Medan, and its customers. Customers of Jinjja Chicken Medan were surveyed online. Responses are collected through purposive sampling and analysed using SPSS V.25. The test revealed that customer loyalty in Jinjja Chicken Medan is influenced by service quality and price.